Effects of silent brain infarction on the hemorrhagic transformation and prognosis in patients with acute ischemic stroke after intravenous thrombolysis - Zhang, Lulu; Wang, Shan; Qiu, Lanfeng; Jiang, Juean; Jiang, Jianhua; Zhou, Yun; Ding, Dongxue; Fang, Qi (Frontiers in Neurology, 2023)
Background: Silent brain infarction (SBI) is a special type of stroke with no definitive time of onset, which can be found on pre-thrombolysis imaging examination in some patients with acute ischemic stroke (AIS). However, the significance of SBI on intracranial hemorrhage transformation (HT) and clinical outcomes after intravenous thrombolysis therapy (IVT) is uncertain. We aimed to explore the effects of SBI on intracranial HT and the 3-month clinical outcome in patients with AIS after IVT. Methods: We consecutive collected patients who were diagnosed with ischemic stroke and received IVT from August 2016 to August 2022, and conducted a retrospective analysis in this study. The clinical and laboratory data were obtained from hospitalization data. Patients were divided into SBI and Non-SBI groups based on clinical and neuroimaging data. We use Cohen's Kappa to assess the interrater reliability between the two evaluators, and multivariate logistic regression analysis was used to further assess the association between SBI, HT and clinical outcomes at 3 months after IVT. Results: Of the 541 patients, 231 (46.1%) had SBI, 49 (9.1%) had HT, 438 (81%) had favorable outcome, 361 (66.7%) had excellent outcome. There was no significant difference in the incidence of HT (8.2 vs. 9.7%, p = 0.560) and favorable outcome (78.4% vs. 82.9%, p = 0.183) between patients with SBI and Non-SBI. However, patients with SBI had a lower incidence of excellent outcome than the patients with Non-SBI (60.2% vs. 71.6%%, p = 0.005). After adjustment for major covariates, multivariate logistic regression analysis disclosed that SBI was independently associated with the increased risk of worse outcome (OR = 1.922, 95%CI: 1.229-3.006, p = 0.004). Conclusion: We found that SBI was no effect for HT after thrombolysis in ischemic stroke patients, and no effect on favorable functional outcome at 3 months. Nevertheless, SBI remained an independent risk factor for non-excellent functional outcomes at 3 months.